Dietary Chlorella vulgaris Improves Growth and Modulates Gut Microbiota in Giant Freshwater Prawn (Macrobrachium rosenbergii) - Norazman, Ammar; Tahir, Nur Diyana Mohamad; Salleh, Annas; Nor, Norhariani Mohd; Azmai, Mohamad Noor Amal; Ikhsan, Natrah (Universitas Airlangga, 2025)
The giant freshwater prawn (Macrobrachium rosenbergii) is a commercially vital species in global aquaculture due to its rapid growth and high market demand, and Chlorella vulgaris is a nutrient-rich microalga lauded for its potential as a sustainable feed supplement. In this preliminary study, the effects of C. vulgaris supplementation on the growth and gut microbiota of giant freshwater prawn was investigated. Prawns were randomly assigned to three groups and fed diets supplemented with C. vulgaris at 0 g/kg (control), 30 g/kg (T1), or 60 g/kg (T2) for 14 days. For growth performance analysis, body weight was measured in a randomly selected 10% of the population at the beginning, midpoint, and end of the experiment. For gut microbiota analysis, faecal samples were taken from M. rosenbergii and used for DNA extraction and amplification via PCR. The PCR product was sequenced using 16S rRNA sequencing on Illumina platform. Results showed significantly improved growth rates in the supplemented groups, with T2 (highest growth rate) having 55% higher weight gain compared to the controls. Gut microbiota analysis revealed increased diversity, with the alpha biodiversity indices showing higher indices in supplemented groups compared to the controls although non-significant (p = 0.196, 0.136, 0.532 and 0.304 for Ace Chao1, Shannon and Simpson respectively). Specifically, the T1 group (highest alpha biodiversity) exhibited the following increases compared to the control: Ace by 53.55%, Shannon by 61.16%, Chao1 by 55.94%, and Simpson by 55.90%. In β-biodiversity analysis, there were shifts in bacterial community composition, with a notable increase in beneficial bacteria such as Synechocystis spp. and decrease in potentially pathogenic ones such as Chitinibacter spp. in the supplemented groups. PICRUSt2 analysis predicted enhanced metabolic pathways related to vitamin synthesis and energy metabolism, suggesting improved gut health and nutrient utilization. Although some results lacked statistical significance due to the short study duration, the findings suggest that long-term C. vulgaris supplementation may yield more pronounced benefits in M. rosenbergii aquaculture, potentially improving growth performance.